PENDOKUMENTASIAN TENTANG PERENCANAAN DAN PELAKSANAAN ASUHAN KEPERAWATAN DI RUANG BAROKAH RUMAH SAKIT PKU MUHAMMADIYAH GOMBONG - indrajati, indah; ummah, m. basirun al; Sumarsih, Tri (Jurnal Ilmiah Kesehatan Keperawatan, 2011)
The implementation of nursing documentation process is nursesâ€™ responsibility. Based on the results of preliminary study, it was found that the nursing care documentation was still incomplete in the nursing assessment and there was an incompatibility with the implementation in Barokah Ward PKU Muhammadiyah Gombong Hospital. The aim of this study is to find out the implementation of documentation regarding the nursing care planning and implementation in Barokah ward of PKU Muhammadiyah Gombong Hospital. The data were analyzed by using unyvariate (descriptive) quantitative with cross sectional approach. This research was conducted in June 2010. There were 14 respondents used as the samples and taken by using total sampling technique. The data were collected by observation. In planning documentation, there were 8 respondents (53.33%) got enough category, 7 respondents (46.60%) got less category. In nursing care implementation, there were 10 respondents (60.00%) got enough category and 5 respondents (40.00%) got less category. the overall results show that the implementation of documentation regarding the nursing care planning and implementation was in enough category. Â  Keywords: documentation, correspondence, nursing care